The Possible Outcomes of Poor Adherence to Conventional Treatment in Patients with X-Linked Hypophosphatemic Rickets/Osteomalacia - Hiroaki Zukeran; Kento Ikegawa; Chikahiko Numakura; Yukihiro Hasegawa (Endocrines, 2023)
X-linked hypophosphatemic rickets/osteomalacia is an inherited disease caused by the loss of function in PHEX. Elevated plasma FGF23 in patients with XLH leads to hypophosphatemia. The conventional treatment for XLH, consisting of oral phosphate and active vitamin D, is often poorly adhered to for various reasons, such as the requirement to take multiple daily doses of phosphate. Burosumab, an anti-FGF23 antibody, is a new drug that directly targets the mechanism underlying XLH. We report herein three adult patients with poor adherence to the conventional treatment. In Patient 1, adherence was poor throughout childhood and adolescence. The treatment of Patients 2 and 3 became insufficient after adolescence. All of the patients suffered from gait disturbance caused by pain, fractures, and lower extremity deformities early in life. We prescribed burosumab for the latter two patients, and their symptoms, which were unaffected by resuming conventional treatment, dramatically improved with burosumab. Maintaining adherence to the conventional treatment is crucial but challenging for patients with XLH. Starting burosumab therapy from childhood or adolescence in pediatric patients with poor adherence may help prevent the early onset of complications.